MY culture wise application - Fung, Viliannie; Ramji, Irdhina Hani; Janis, Jerad Jay; Gatu, Alvin (Universiti Teknologi MARA, Perak, 2023)
Each year, millions of tourists travel to Malaysia, drawn by its diverse and culturally vibrant landscape. However, for a harmonious and respectful relationship with the local community, visitors must comprehend and honour the multitude of cultural beliefs prevalent in Malaysia. By adhering to these customs, tourists can steer clear of unintentional offences and foster meaningful cultural exchanges, resulting in unforgettable experiences. Thus, the MY Culture Wise application has been developed to enhance traveller experiences and nurture cross-cultural understanding, particularly in Sabah. This app serves as a guide, equipping tourists with up-to-date information to navigate the intricate tapestry of Malaysian cultural norms. It encompasses guidelines on appropriate attire, social interactions, and practices for respecting religious and cultural traditions. Additionally, users can access location-specific cultural insights, making it a valuable resource for anyone exploring Malaysia. To ensure widespread adoption, extensive promotion of the application will take place across various social media platforms. Furthermore, collaboration with the Visitor Information Board will beestablished in every state. These partnerships will serve to elevate the visibility and distinguish the MY Culture Wise app within the market, leveraging the presence of Visitor Information Centers as strategic venues to engage with visitors and encourage app downloads. By facilitating cultural understanding and empowering tourists to make informed decisions, the MY Culture Wise application endeavours to create a more respectful and enriching travel experience for all. Its inclusive approach and collaborative efforts aim to bridge the gap between visitors and local communities, fostering mutual appreciation and celebration of Malaysia's diverse heritage.